Dance pedagogy for a diverse world culturally relevant teaching in theory, research and practice - McCarthy-Brown, Nyama (McFarland & Company, Inc., Publishers, 2017)
This book provides dance educators with tools to refocus teaching methods to celebrate the pluralism of the United States. The contributors discuss how to diversify dance history courses in higher education and ballet technique classes, choreographing dance about socially charged contemporary issues and incorporating Native American dances into the curriculum, among other topics